Clinical and subclinical characteristics of ovarian tumors in pregnant women at Thai Binh Obstetrics and Gynecology Hospital from 2015 to 2019 (Vietnam Journal of Community Medicine, 2022)
The study was carried out on 205 medical records that were diagnosed with ovarian tumors in pregnant women who met the criteria at the record archive of Thai Binh Obstetrics and Gynecology Hospital. The results showed that ovarian tumors < 5cm in size accounted for the highest rate of 74.1%. Dermoid cysts are the most common among common tumors, accounting for 45.9%. Torsion occurs mainly in the first 3 months of pregnancy. UBT properties on ultrasound: 56.1% of cases are described on ultrasound. In which: 42.6% sound sparse, 90.4% regular border and 13.9% with septum and papillary. 42.3% were discovered by chance at antenatal care and ultrasound.
Keywords: Ovarian tumors, pregnant women.